Mudir Leadership in Improving Teachers’ Discipline at One Pondok Pesantren in Jambi - MOHAMAD MUSPAWI (Ta'dib: Jurnal Pendidikan Islam, 2018)
This study aimed at determining the principals (Mudir) leadership in improving teachers’ discipline at óne Islamic boarding school (Pesantren) in the city of Jambi, Indonesia. Specific targets to be achieved from this research were guided by two research quetions: 1) how is the Mudir leadership in improving the discipline of teachers? and 2) what are the obstacles of Mudir leadership in improving teachers’ discipline? The research method used was qualitative method with a case study approach, where I described the research findings in the form of narrative ways. Data collection techniques used in this research were obervation, documentation, and interview. In relation to the trustworthness of the reseach, I applied triangulation through observation, documentation, and interviews. In addtition, member checking and audit-trail were used. In analyzing the data, I trancribed the data, coded, and put them into some themes. I translated the thematic data into English and presented the data in a descriptive way. The findings of the study informed that the Mudir have applied some acts to improve teachers’ discipline namely being an exemplary person with discipline, evaluating teachers’ discipline, giving reward and punishment, and doing class visits. Some obstacles revealed in this research were physical performance of the Mudir and teachers’ age.